1995
DOI: 10.1248/bpb.18.876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roxithromycin on Proliferation of Peripheral Blood Mononuclear Cells and Production of Lipopolysaccharide-Induced Cytokines.

Abstract: Roxithromycin (RXM), a new macrolide antibiotic, has a 14-member macrocycline ring structure which is similar to that of erythromycin. We investigated the effects of RXM on the proliferation of peripheral blood mononuclear cells (PBMCs) and the production of interleukin 1 beta (IL-1 beta) and tumor necrosis factor alpha (TNF-alpha) by PBMCs stimulated with lipopolysaccharide (LPS). At concentrations greater than 25.0 micrograms/ml, RXM suppressed the proliferation of PBMCs stimulated with phytohemagglutinin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It has been shown in in vitro studies that macrolides modulate the proliferation, differentiation, cytokine production and phagocytosis of monocytes, macrophages and lymphocytes [25][26][27][28][29][30][31]. Macrolides also improve the ciliary movement of airway epithelial cells [32], inhibit bacterial adherence to ciliated epithelial cells [33], suppress IL-8 production from airway epithelial cells and exudative neutrophils [34][35][36] and inhibit glycoprotein and electrolyte secretion from airway epithelial cells and nasal gland cells [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in in vitro studies that macrolides modulate the proliferation, differentiation, cytokine production and phagocytosis of monocytes, macrophages and lymphocytes [25][26][27][28][29][30][31]. Macrolides also improve the ciliary movement of airway epithelial cells [32], inhibit bacterial adherence to ciliated epithelial cells [33], suppress IL-8 production from airway epithelial cells and exudative neutrophils [34][35][36] and inhibit glycoprotein and electrolyte secretion from airway epithelial cells and nasal gland cells [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Roxithromycin, for example, inhibits the production of interleukin (IL)-1b and tumor necrosis factor (TNF)-a in human peripheral blood monocytes in a dose-dependent manner [5]. Roxithromycin also has an inhibitory effect on IL-8 and on intercellular adhesion molecule (ICAM)-1 expression in human bronchial epithelial cells [6].…”
mentioning
confidence: 99%
“…We did not find any reports about the genotoxic potential of RXM, although in our unpublished study, RXM did not show any genotoxic effect in human lymphocytes in chromosome aberration, sister chromatid exchange, and micronucleus tests. When we talk about cytotoxicity of RXM, there are some studies showing the anti-proliferative effect of RXM (Dai et al, 2014;Yatsunami et al, 1999;Yoshimura et al, 1995). On the contrary, one study reported that RXM had anti-cytotoxic effect against sulfur mustard in human respiratory epithelial cells (Gao et al', 2007).…”
Section: Introductionmentioning
confidence: 99%